UNTRADITIONAL METHODS OF P-APPLICATION FOR RAISING ITS EFFICIENCY ON SANDY SOIL - K Nassar; M El-Shouny; S El-Fiki (Arab Universities Journal of Agricultural Sciences, 2005)
Soils of Egypt characterize with raising pH values, CaCO3 content, clay and Fe & Al oxides. These factors contribute, to a large extent, in P-fixation in soil and its transformation into unavailable forms. This reflect, in turn, on plant growth and the resultant crop. So, the main target of this investigation is raising the use efficiency of P-fertilization, decreasing P-fixation, increasing its availability in soil and promoting its uptake by plant through testing new methods for P-application compared with the traditional one (P-application before sowing). Therefore, two field experiments were designed in sandy soils during the two winter seasons 2002/2003 and 2003/2004 at South Tahrir Res. Station, Ali Moubark village, El-Bustan region, Behira gover-norate under drip irrigation system. For the two experiments, P was applied as soil or seed coating. Soil application treatments were added at a rate of 30 kg P2O5/fed., once before sowing, twice: before sowing and during the vegetative growth stages or in three portions, before sowing and during the vegetative and flowering growth stages. In seed coating method, seed were coated before sowing with P at rates of 0.1, 0.2 and 0.3 kg P2O5/kg seed. Data obtained revealed that the treatments of P-soil application generally surpassed the P-seed coating ones. In this respect, P-soil appli-cation in three portions (at sowing and during the vegetative and flowering growth stages) gave the highest increments in seed, straw and seed protein yields as well as macro- and micronutrients contents in both seed and straw compared with the tradi-tional method of soil P-application. Moreover, seed coated with 0.2 kg P2O5/kg seeds attained the highest increases in all abovementioned yield components and nu-tritive contents among the treatments of seed coating method, whereas, coating of seeds with 0.3 kg P2O5/kg seeds caused the least ones. Therefore, it can be conclud-ed that the addition of P to sandy soil at a rate of 30 kg P2O5/fed., in three portions, i.e. at sowing and during the vegetative and flowering growth stages reduce P-fixation by soil factors, increase its availability, promote its uptake by plant, achieve the highest productivity of faba bean seed, straw and seed protein yields and im-prove the nutritive contents of both seeds and straw.